Capacity Building dalam Penguatan Manajemen Pesantren - Sofwan Manaf; Ahmad Farid; Hadiyanto Arief; Samiyono (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the implementation of capacity building in pesantren management, focusing on strengthening human resources, institutional development, and the adaptation of curriculum and technology in line with 21st-century developments. For data analysis techniques, a thematic analysis approach is used. Data obtained from interviews, observations, and documents will be analyzed to identify the main themes related to the implementation of capacity building. This process involves coding the data, categorizing information, and interpreting the findings in the context of the research objectives. The results of the study show that strengthening human resources through training and workshops is crucial for improving the managerial skills of pesantren administrators. In addition, the adaptation of a technology-based curriculum is also a key factor in improving the quality of education in pesantren, allowing students to be better prepared to face global and digital world challenges. Overall, this study concludes that systematic and sustainable capacity building in pesantren will strengthen institutional capacity, improve competitiveness, and maintain the relevance of pesantren in facing the challenges of modern times. The proper implementation of capacity building will enable pesantren not only to serve as centers for religious education but also as adaptive, innovative educational institutions capable of contributing to the socio-economic development of the community.